Menelusuri Gejolak dan Antusiasme Tren Pencarian Genre Musik di Indonesia dari 2018 sampai 2023 - Akbar Bagaskara; Umilia Rokhani; Kustap (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2023)
Purpose: The purpose of this research is to analyze the search trends of music genres in Indonesia in the period of 2018-2023. In this study, four popular music genres in Indonesia were used as analysis samples, namely; Islamic music, jazz music, rock music, and dangdut music. Method: The method used is a qualitative type, which acts to describe the data narrative read from the google trends tool which also functions as a data analysis instrument. Result and Discussion: The results of this research found; that (1) The search trend for dangdut was very popular in the duration of 2018-2023 beating the three other music genres, even the search trend for dangdut music dominated in almost every province in Indonesia (2) The search trend for jazz music and rock music competed fiercely in the period 2018-2023, overtaking each other in that period. (3) In terms of graphical appearance, the trend of Islamic music does not seem to increase much compared to the search trends of the other three music genres throughout the last five years (2018-2023) (4) Central Java and Lampung provinces always appear in the top five provinces in the search trends of Islamic music, jazz music, rock music, and dangdut genres. Conclusion: The conclusion obtained in this study is that the search trend for certain music genres is strongly influenced by the culture or group of people who have an attachment to it. The more the music genre can enter many groups of society, the more fans there will be and of course this will increase the search trend for the music genre on social media, as discussed in this study.